Learning Strategies at SD Muhammadiyah 2 Krian during the Covid 19 Pandemic - Muhlasin Amrullah; Fitriani Setya Kirana Rochmaeni (Proceedings of The ICECRS, 2021)
This study aims to determine the strategies used by Muhammadiyah 2 Krian Elementary School in learning during the Covid-19 pandemic. The method used by author is qualitative research and using a phenomenological approach to explore information related to the issues raised. Muhammadiyah 2 Krian Elementary School carries a new learning strategy asa solution in dealing with the Covid-19 pandemic, namely learning online using the WhatsApp application, google meet, and zoom. However, the method was not effective enough that the Muhammadiyah 2 Krian Elementary School teachers implemented a visiting teacher system and a consultation class. With the implementation of this strategy as a solution in dealing with learning during the Covid-19 pandemic, teaching and learning activities at the Muhammadiyah 2 Krian Elementary School can run well.